Test Method for Compression Resilience Evaluation of Textiles - Bao-guo Yao; Li-xia Yan; Jian-chao Wang; Shui-yuan Hong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A test method was proposed and a measurement system was developed to characterize the compression resilience properties of textiles based on the mechanical device, microelectronics, sensors and control system. Derived from the typical pressure-displacement curve and test data, four indices were defined to characterize the compression performance of textiles. The test principle and the evaluation method for compression resilience of textiles were introduced. Twelve types of textile fabrics with different structural features and made from different textile materials were tested. The one-way ANOVA analysis was carried out to identify the significance of the differences of the evaluation indices among the fabrics. The results show that each index is significantly different among different fabrics. The denim has the maximum compressional resilience and the polar fleece has the minimum compressional resilience. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1992